SEGMENTASI PASAR JASA PENDIDIKAN - Ambarwati, Puji; Muin, Abdul; Zohriah, Anis (STKIP Pesisir Selatan, 2024)
Nowadays, we can see that schools, both public and private, have been established in many villages and cities. Competition has also increased. These schools began competing to offer various advantages that can be obtained by the community, ranging from interesting activity programs, achievements that have been achieved, complete facilities to affordable prices. However, in the end, there were still schools that began to be quiet, and did not get students until they were forced to close. Although schools are non-profit institutions, they must still be managed professionally so that their purpose is to help educate the nation's children, improve the quality of human resources and create superior generations in the future can run optimally. In responding to this, a marketing strategy is needed, one of the techniques is to segment the market. Market segmentation in the context of educational services is an attempt to divide a heterogeneous market into more homogeneous groups. This can be done based on the same characteristics, interests, needs and level of socio-economic status. This research uses literature study techniques by searching for data and information through books and scientific journals. This research aims to contribute to the development of marketing strategies in the education sector and provide practical implications for managers of educational institutions in designing more effective marketing strategies.